Effect of trivalent arsenicals on cell proliferation in mouse and human microvascular endothelial cells. (2015) - Dodmane, Puttappa R.; Arnold, Lora L.; Pennington, Karen L.; Singh, Rakesh K.; Cardoso, Ana Paula Ferragut; Cohen, Samuel M.
Abstract: Chronic exposure to high levels of inorganic arsenic (iAs) has been associated with cancerous and non-cancerous health effects, including cardiovascular effects. However, the mechanism for a presumed toxic effect of arsenic on vascular tissue is not clear. Our working hypothesis is that inorganic trivalent arsenic and its methylated metabolites react with cysteine-containing cellular proteins and alter their function leading to adverse events such as cytotoxicity or proliferation. In this study, human microvascular endothelial cells (HMEC1) and mouse microvascular endothelial cells (MFP-MVEC) were exposed to arsenite (iAs III ), monomethylarsonous acid (MMA III ), or dimethylarsinous acid (DMA III ) for 72 h to evaluate cytotoxicity, and for 24, 48 or 72 h to evaluate cell proliferation. Both cell lines showed similar LC50 values, from 0.1 to 2.4 μM, for all three trivalent arsenicals. The endothelial cells treated with1 nM to 1 μM concentrations of the three trivalent arsenicals did not show increased cell proliferation at 24, 48 or 72 h or increased rate of proliferation at 72 h of exposure. Overall, cytotoxicity of trivalent arsenicals to microvascular endothelial cells is similar to their cytotoxicity to epithelial cells, and that these compounds are not mitogenic.